1977
DOI: 10.1246/bcsj.50.2917
|View full text |Cite
|
Sign up to set email alerts
|

Linear-sweep Voltammetry and the Simultaneous Determination of Purine Bases and Their Nucleosides in the Glassy Carbon Electrode

Abstract: Adenine, adenosine, guanine, and guanosine were voltammetrically oxidized in a glassy carbon electrode in aqueous solutions, but at different potentials. In general, the nucleosides were oxidized at more positive potentials than their bases. The bases and their nucleosides were strongly adsorbed on the surface of the glassy carbon electrode at the pH values around neutrality, so that the concentration vs. anodic peak current curves were not linear. The adsorption on the electrode was very dependent on the pH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…Compound 1 gave a single, well-defined oxidation peak over the pH range (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) investigated ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound 1 gave a single, well-defined oxidation peak over the pH range (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) investigated ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] The redox chemistry of these nitrogen heterocycles is important because they constitute the essential components of polynucleic acids and other biologically important compounds, such as ATP and GTP. In addition, some authors have suggested that the electrochemical and enzymatic oxidations of purines follow similar mechanistic pathway^.^,^ It was therefore of interest to examine the electrochemistry of a recently developed deoxyguanosine analogue, 9-[1,3-dihydroxy-2-propoxymethyl]guanine ( l).7 This compound is a potent antiviral agent with a broad range of activity against herpes simplex virus types 1 and 2,*3 cytomegalovirus,g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The anodic signal of xanthine and some methyl-substituted xanthines was studied on carbon electrodes and the results were summarized in details by Dryhurst [4]. It was supposed that the oxidation of these purine derivatives involves electron exchange at carbon C8 and nitrogen N7 at higher oxidation potentials [5][6][7]. The electrooxidation of these substances was studied later by the authors [8][9][10][11][12], who revised the previous results, suggested a detailed oxidation mechanism and described the effect of methyl groups on the oxidation of xanthine [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical method had also been devised for the detection of adenosine. Yao et al [8] reported the simultaneous determination of purine bases and their nucleosides at glassy carbon electrode. However the electrooxidation of adenosine on the common working electrode showed high oxidation potential and limited sensitivity.…”
Section: Introductionmentioning
confidence: 99%